Class III Restoration of Anterior Primary Teeth: In Vitro Retention Comparison of Conventional, Modified and Air-abrasion Treated Preparations - Asl Aminabadi, Naser (Tabriz University of Medical Sciences, 2014)
Background and aims. Anterior esthetic restoration is challenging in pediatric dentistry, due to limited durability and poor retention of the restoration.This study assessed the effect of air abrasion on tensile failure load of composite class III restorations using different preparation techniques. Materials and methods. 100 extracted human anterior primary teeth were divided, based on the preparation methods, into four groups each consisting of 25 subjects : conventional (A), labial surface bevel (B), conventional + air abrasion (C), and labial surface bevel + air abrasion (D). After restoring cavities, tensile failure load of samples was measured in Newton by Universal testing machine at a crosshead speed of 1 mm per minute. The data were analyzed by Kruskal-Wallis and Mann Whitney U tests using SPSS software. Results. There were statistically significant differences between groups A and C (P = 0.003), groups A and B (P & 0.001), groups A and D (P & 0.001), groups B and C (P = 0.028), groups B and D (P = 0.027), and also groups C and D (P& 0.001). Group D demonstrated the highest mean tensile failure load. Conclusion. Labial surface bevel treated by air abrasion showed significantly more retention of composite restoration.